# Math

Solve for x:

e^4x-3 = 2e^2x1

ln2x+6) - ln(3x-1) = ln(2)

e^(4x-3) = 2e^(2x)
No idea what the final 1 is. Anyway, I'll work this, and then you can fix it if necessary.

Taking logs of both sides, we get

4x-3 = ln2 + 2x
2x = 3+ln2
x = (3+ln2)/2

ln(2x+6) - ln(3x-1) = ln(2)
(2x+6)(3x-1) = 2

posted by Steve

## Similar Questions

1. ### Linear Algebra

Solve the following system using Gauss's algorithm (a) x1 + 2x2 + 4x3 + 6x4 = 3 2x1 + x2 + 3x3 = -6 -2x1 + x2 + 6x3 + 4x4 = -11 2x1 + x2 + x3 = 0 so the matrix will be: 1 2 4 6 3 2 1 3 0 -6 -2 1 6 4 -11 2 1 1 0 0
2. ### linear algebra

If possible, solve the following linear systems by Cramer's rule. 2x1 + 4x2 + 6x3 = 14 x1 + 2x3 = 0 2x1 + 3x2 − x3 = 30
3. ### linear

If possible, solve the following linear systems by Cramer's rule. 2x1 + 4x2 + 6x3 = 14 x1 + 2x3 = 0 2x1 + 3x2 − x3 = 30 i am having trouble with this one
4. ### math

use simplex method solbe LPP maximize Z=2x1+4x2+x3+x4 subject to x1+3x2+x4<4 2x1+x2<3 x2+4x3+x4<3 x1,x2,x3,x4>0
5. ### math

use simplex method solbe LPP maximize Z=2x1+4x2+x3+x4 subject to x1+3x2+x4<4 2x1+x2<3 x2+4x3+x4<3 x1,x2,x3,x4>0
6. ### Linear Programming

calculate the lower bound from min z= 4x1 + 2x2 2x1 - 3x2 => 4 x1 + 5x2 <= 6 2x1 - 6x2 = 10 x1=>0